Studi Terhadap Hadis-Hadis Tentang Qurban Terdapat Pada Buku Pedoman Ke Al-Azharan - Ardi, Ardi; Safri, Edi; Fithri, Widya (Institut Agama Islam Sumatera Barat Pariaman, 2025)
This study aims to trace the status and quality of hadith about qurban and its understanding as stated in the Al-Azharan Guidebook, which is the official guide for students in the Al-Azhar Foundation. The method used is descriptive qualitative with a library research approach. The main source of this research is the Al-Azharan Guidebook, while supporting sources include Mu'jam Al-Mufahras lil Al-Hadith Al-Nabawiy, Sunan Abu Daud, hadith commentaries, rijalul hadith literature, and relevant scientific articles. Digital data searches were conducted through Dimensions and Google Scholar, while visualisation of relationships between journals was analysed using the VOSviewer application. The results showed that the hadith referenced in the book has a valid sanad and a valid matan, with all its narrators categorised as tsiqah by hadith scholars. The hadith confirms the validity of the qurban after the Eid al-Adha prayer and explains the special case of Abu Burdah as an exception. The book shows a tendency towards a textual understanding of the hadith, focusing on adherence to the shar'i procedures of qurban. However, there are shortcomings in the presentation of the hadith, especially the lack of a complete sanad and matan, which could potentially lead to misunderstandings. Therefore, it is recommended that the presentation of hadith in education books should be done fully and accurately to maintain the integrity of students' religious understanding.